Arduino/Genuino: start as professional: short course in a book - Alsibai, Mohammed Hayyan; Sulastri, Abdul Manap (Penerbit UMP, 2017)
Do you know: Open source, Prototyping, Electronics? Arduino is a microcontroller. It is an open-source project which created kits for prototyping and building control devices and interactive tools that can sense and control devices. If you understand nothing from the previous lines, be happy! This book is written mainly for you.